2014
DOI: 10.1073/pnas.1315126111
|View full text |Cite
|
Sign up to set email alerts
|

Afforestation in China cools local land surface temperature

Abstract: China has the largest afforested area in the world (∼62 million hectares in 2008), and these forests are carbon sinks. The climatic effect of these new forests depends on how radiant and turbulent energy fluxes over these plantations modify surface temperature. For instance, a lower albedo may cause warming, which negates the climatic benefits of carbon sequestration. Here, we used satellite measurements of land surface temperature (LST) from planted forests and adjacent grasslands or croplands in China to und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
447
3
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 593 publications
(479 citation statements)
references
References 26 publications
26
447
3
3
Order By: Relevance
“…In humid regions (P/PET41) where PET plays a dominant role in water yield or evapotranspiration, a decrease in PET will likely cause a significant increase in water yield. This is consistent with the findings that afforestation can increase water yield in large watersheds of humid regions 11,12 because afforestation cools local land surface temperature 39 and thus decreases PET.…”
Section: Discussionsupporting
confidence: 91%
“…In humid regions (P/PET41) where PET plays a dominant role in water yield or evapotranspiration, a decrease in PET will likely cause a significant increase in water yield. This is consistent with the findings that afforestation can increase water yield in large watersheds of humid regions 11,12 because afforestation cools local land surface temperature 39 and thus decreases PET.…”
Section: Discussionsupporting
confidence: 91%
“…The feedback between land cover change and regional climate has attracted much attention in recent studies on regional climate variability caused by afforestation [46], and conclusions vary at regional to global scales. Understanding the interactions between the land and atmosphere can facilitate sustainable development of the ecological environment.…”
Section: Role Of Ecological Restoration In Vegetation Dynamicsmentioning
confidence: 99%
“…Undoubtedly, changes in vegetation directly or indirectly modify biosphere-atmosphere interactions, including the hydrological cycle and energy budgets Chapin et al, 2005). A recent research has shown that vegetation growth cools local land surface temperature (Peng et al, 2014;Shen et al, 2015). However, the increased vegetation coverage result in changes in water resources, which is a dominant factor for fragile ecological regions, through inducing changes in land surface energy components, has not been well documented.…”
Section: Introductionmentioning
confidence: 99%